Naḥw Studies in Jambi: Exploration of Local Manuscripts on its Origin and Existence - Rosalinda, Rosalinda; Tarmizi, Ahmad; Nurdin, Nurdin; Ilham, Andri (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
The Arabic language, particularly naḥw (syntax), is considered highly important to the Malay people, including those in Jambi. However, the study of naḥw in the manuscripts available in Jambi remains very limited. This article explores the study of naḥw in Jambi by mapping naḥw manuscripts housed in the Siginjei Museum and the Gentala Arsy Museum in Jambi. This research employs a facsimile text edition approach to the naḥw manuscripts with registration numbers 2505, 2539, 2514, 2540, and 2160. The findings reveal that the naḥw manuscripts in the collections of the Siginjei and Gentala Arsy Museums in Jambi have a strong connection with naḥw studies in the Middle East. The naḥw manuscripts in Jambi are not works of Jambi scholars (ulama), but were brought by ulama from outside Jambi, especially from Mecca, such as Sayyid ‘Abdullāh Dahlān who arrived in 1923, Shaykh Sa‘īd Yamanī in 1924, and others who taught at Madrasah Nurul Iman. Additionally, there are manuscripts that were brought from Palembang to Jambi. The naḥw manuscripts in Jambi generally contain and record the content of al-‘Awāmil al-Mi’ah by ‘Abd al-Qāhir al-Jurjānī. However, the book is not used as a naḥw textbook in the pesantren in Jambi. Ilmu bahasa Arab, naḥw khususnya, dianggap sangat penting bagi orang Melayu, termasuk Jambi. Namun kajian ilmu nahwu dalam manuskrip yang ada di Jambi masih sangat minim. Artikel ini menelusuri kajian naḥw di Jambi melalui pemetaan manuskrip Nahwu yang ada di Museum Siginjei dan Museum Gentala Arsy Jambi. Penelitian ini menggunakan edisi teks faksimili terhadap manuskrip naḥw dengan nomor registrasi 2505, 2539, 2514, 2540, and 2160 dan melakukan wawancara dengan sejumlah pengurus pondok pesantren. Dari hasil penelusuran diketahui bahwa manuskrip naḥw koleksi Museum Siginjei dan Gentala Arsy Jambi memiliki hubungan yang kuat dengan kajian naḥw Timur Tengah. Manuskrip naḥw yang ada di Jambi bukan merupakan karya ulama Jambi, melainkan dibawa oleh ulama dari luar Jambi, khususnya dari Mekkah, seperti Sayyid ‘Abdullāh Dahlān yang datang pada tahun 1923, Shaykh Sa‘īd Yamanī pada tahun 1924, dan lainnya yang mengajar di Madrasah Nurul Iman. Selain itu, ada juga manuskrip yang dibawa dari Palembang ke Jambi. Manuskrip naḥw di Jambi umumnya banyak memuat dan mencatatkan isi dari kitab al-‘Awāmil al-Mi’ah karya ‘Abd al-Qāhir al-Jurjānī. Namun, kitab tersebut tidak digunakan sebagai kitab nahwu di pesantren-pesantren yang ada di Jambi.